Implementasi Cross-Curricular Learning untuk Meningkatkan Literasi di Sekolah Dasar Berbasis Agama - Purnairawan, Riski Eka; Anfasa, Muhammad Farid (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This study aims to examine the implementation of cross-curricular learning in enhancing literacy skills at MIN 1 Trenggalek (an  Islamic elementary school), focusing on how the integration of subjects such as environmental awareness, Indonesian language, and Islamic religious education supports the development of literacy, critical thinking, and collaboration skills. This study also identifies the challenges encountered in implementation and provides practical recommendations for educators and policymakers.Method – A qualitative descriptive approach was employed, using interviews, observations, and document analysis to gather data from teachers and administrators. Triangulation was used to validate the findings. Data analysis involved reducing, presenting, and verifying the data to draw meaningful conclusions.Findings – The findings at MIN 1 Trenggalek reveal that implementing cross-curricular learning through thematic integration, which combines multiple subjects under a relevant topic such as the theme "Water and Life" involving science, mathematics, and Indonesian language, effectively enhances students' literacy, critical thinking, and collaboration skills. Students also actively participate in practical and extracurricular activities, such as community clean-up initiatives under the theme "Environmental Cleanliness and Health," which connect science, civics, and reflective writing tasks. This approach not only strengthens students’ academic skills but also integrates religious values into real-life contexts, creating meaningful and applicable learning experiences. Research Implications – This study highlights the potential of cross-curricular learning in faith-based primary schools to improve academic and spiritual literacy. It emphasizes the need for structured teacher training to ensure effective implementation aligned with institutional values.